Financial Management Strategies to Improve Business Performance - Salamah, Siti Nuraeni (ADMAN: Journal of Contemporary Administration and Management, 2023)
In the business world, company performance is very important. Business performance is influenced by various factors such as strategy, human resource management, financial management, and business environment. Effective and efficient financial management is essential to ensure business sustainability and growth. The purpose of this study is to discuss appropriate financial management strategies to improve business performance. The methodology used in this study is descriptive analytical method using secondary data obtained from various sources such as academic journals, books, and company financial reports. This study arrives at the conclusion that in an increasingly complex and competitive business era, effective financial management is an important key in improving company performance. The right financial management strategy can help companies estimate and allocate resources effectively, manage risks, and make the right decisions in capitalising on business opportunities.